Isolation of aphrodisiac active fraction from sanrego bark (Lunasia amara Blanco) - ., Arnida; Donatus, Imono A.; Wahyuono, Subagus (Indonesian Journal of Pharmacy, 2003)
Sanrego (Lunasia amara Blanco) bark is traditionally utilized as an aphrodisiac although scientifically has yet been proven. Therefore, this study is aimed to prove aphrodisiac activity, determine the compounds and the dose of the active fraction. Initially sanrego bark (600 g) was extracted in a Soxhlet apparatus with methanol (MeOH) to give MeOH extract (A, 80 g). The MeOH extract was fractionated by Ethylacetate (EtOAc) to give EtOAC soluble (B, relatively non-polar, 15.23 g) and EtOAc insoluble (C, relatively polar, 50.20 g). The aphrodisiac test was performed in male Wistar rats that were divided into 6 groups (5 rats each) [I, treated with Na-CMC 0.5%, 50 mg/kg BW; II, yohimbine, 5 mg/kg BW; III, distilled water , 2 ml/200 g BW; IV, extract A; V, fraction B; VI, fraction C], and the doses given to groups IV-VI were similar (10, 50, 100, and 200 mg/kg BW). The male’s behaviors to female rats ( introduction, climbing and coitus ) were recorded and analysed at p= 0.5. Determination of the active compounds were performed by thin layer chromatography (TLC) using various detection reagents. The result indicated that the highest aphrodisiac effect was demonstrated by fraction B, followed by extract A and fraction C . Fraction B demonstrated introduction (84.2%), climbing (84.9%) and coitus (85.2%). TLC profile suggested that fraction B contain alkaloids and terpenoids as the main components.Keywords: Sanrego bark, Lunasia amara, Aphrodisiac, Active fraction .